2008
DOI: 10.1158/1535-7163.mct-07-0445
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism of drug resistance in breast cancer cells: fatty acid synthase overexpression-mediated palmitate overproduction

Abstract: Multidrug resistance is a major problem in successful cancer chemotherapy. Various mechanisms of resistance, such as ABC transporter-mediated drug efflux, have been discovered using established model cancer cell lines. While characterizing a drug-resistant breast cancer cell line, MCF7/AdVp3000, we found that fatty acid synthase (FASN) is overexpressed. In this study, we showed that ectopic overexpression of FASN indeed causes drug resistance and that reducing the FASN expression increased the drug sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 27 publications
5
158
0
7
Order By: Relevance
“…Fatty acids were used by proliferating tumor cells for membrane assembly, lipid modifications of proteins, and as an efficient source of energy, all are required to sustain neoplasm growth and survival (47). Furthermore, it is shown that FASN is overexpressed in drug-resistant breast neoplasm cell line (MCF7/AdVp3000), and that reducing the expression of FASN increased the drug sensitivity in MCF7 and MDA-MB-468 (breast cancer cell lines) (48). Analogously, FASN was reported to be associated with acquired trastuzumab/docetaxel/5-fluorouracil resistance in breast cancer or radiation and gemcitabine in pancreatic neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids were used by proliferating tumor cells for membrane assembly, lipid modifications of proteins, and as an efficient source of energy, all are required to sustain neoplasm growth and survival (47). Furthermore, it is shown that FASN is overexpressed in drug-resistant breast neoplasm cell line (MCF7/AdVp3000), and that reducing the expression of FASN increased the drug sensitivity in MCF7 and MDA-MB-468 (breast cancer cell lines) (48). Analogously, FASN was reported to be associated with acquired trastuzumab/docetaxel/5-fluorouracil resistance in breast cancer or radiation and gemcitabine in pancreatic neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FASN inhibitor cerulenin demonstrated a strong synergism with docetaxel in HER-2 overexpressing and docetaxel-resistant SK-Br3 cells, which indicated the role of FASN in HER-2-induced breast cancer chemotherapy resistance [80] . FASN blockade also could induce a synergistic chemosensitization of breast cancer cells to other chemotherapy agents, such as paclitaxel, adriamycin, 5-FU and vinorelbine [81][82][83][84] .…”
Section: Targeting Fatty Acid Metabolismmentioning
confidence: 99%
“…Jun-Qin Li & , Hui Xue & , Lan Zhou, Li-Hua Dong, Da-Peng Wei, Hua Li* expression increases drug sensitivity in breast cancer cell lines MCF7 and MDA-MB-468, but not in normal mammary epithelial cell line MCF10A1 (Liu et al, 2008). The present study showed that the overexpression of MEK-5 and cell apoptosis in breast cancer cell line MCF-7-MEK5 with EMT characteristics and TNF-α tolerance occurred when the cells were treated by FASN inhibitor in the overexpression of FASN.…”
Section: Mechanism Of Fatty Acid Synthase In Drug Tolerance Related Tmentioning
confidence: 99%